Orbital superexchange and crystal field simultaneously at play in YVO3: resonant inelastic x-ray scattering at the V L edge and the O K edge - Benckiser, Eva; Haverkort, Maurits W. (Arxiv, 2013)
We report on the observation of orbital excitations in YVO3 by means of resonant inelastic x-ray scattering (RIXS) at energies across the vanadium L3 and oxygen K absorption edges. Due to the excellent experimental resolution we are able to resolve the intra-t2g excitations at 0.1-0.2 eV, 1.07 eV, and 1.28 eV, the lowest excitations from the t2g into the eg levels at 1.86 eV, and further excitations above 2.2 eV. For the intra-t2g excitations at 0.1-0.2 eV, the RIXS peaks show small shifts of the order of 10-40 meV as a function of temperature and of about 13-20 meV as a function of the transferred momentum q||a. We argue that the latter reflects a finite dispersion of the orbital excitations. For incident energies tuned to the oxygen K edge, RIXS is more sensitive to intersite excitations. We observe excitations across the Mott-Hubbard gap and find an additional feature at 0.4 eV which we attribute to two-orbiton scattering, i.e., an exchange of orbitals between adjacent sites. Altogether, these results indicate that both superexchange interactions and the coupling to the lattice are important for a quantitative understanding of the orbital excitations in YVO3.
Gesehen am 24.11.2017
Die Ziffer 3 im Titel ist tiefgestellt